EXTRAetORDINAIRE : Le Printemps de Cahors - Photographie & Arts Visuels. - Ardenne, Paul; Beausse, Pascal; Groys, Boris; Macel, Christine; Perrin, Marie-Thérèse; Piron, François; Reed, Lou; Rosier, Manou; Sami-Ali; T., Ernest (Cahors, 1999)
Adams, Mac ; Aitken, Doug ; Benat, Laetitia ; Blume, Anna & Bernhard Johannes ; Boudier, Véronique ; Bublex, Alain ; Buchanan, Roderick ; Closky, Claude ; Collishaw, Mat ; Courbot, Didier ; Dollinger, Olivier ; Durand, Philippe ; Fischli & Weiss ; Farrell, Malachi ; Framis, Alicia ; Geers, Kendell ; Hains, Raymond ; Kersels, Martin ; Lamarche, Bertrand ; Leccia, Ange ; Lesueur, Natacha ; Lheureux, Christelle ; Locatelli, Martine ; Eric, Made in ; Meste, Philippe ; Mik, Aernout ; Nisic, Natacha ; Rousseau, Samuel ; Shimabuku ; Signer, Roman ; T., Ernest ; Taylor-Wood, Sam ; Wesselo, Erik ; Wurm, Erwin ; Yang, Jun
bibliografie
biografie
Engels
Frans
Frans & Engels
boek